Implementation of Multicultural Values to Strengthen Students' Nationalism - Rakhmawati, Nur Fajrina; Suwarjo, Suwarjo; Basuki, Agus (East Asian Journal of Multidisciplinary Research, 2024)
This study explores the role of multicultural values in strengthening students' nationalism at SMPN 1 Sleman. Through a qualitative descriptive approach using interviews, observations, and documentation, the research found that multicultural values—encompassing diversity, tolerance, and cultural appreciation—are integrated into classroom learning, daily activities, and the Pancasila Student Profile Strengthening Project (P5). These efforts foster attitudes of tolerance, mutual respect, and cultural appreciation, enhancing students' understanding of national identity and unity. By embracing cultural diversity, students develop strong, inclusive personalities, preparing them to face global challenges while maintaining a sense of nationalism.